1997
DOI: 10.1111/j.1558-5646.1997.tb02400.x
|View full text |Cite
|
Sign up to set email alerts
|

EXTINCTION-RECOLONIZATION DYNAMICS IN THE MYCOPHAGOUS BEETLEPHALACRUS SUBSTRIATUS

Abstract: The population structure of the mycophagous beetle Phalacrus substriatus is characterized by many small, local populations interconnected by migration over a small spatial scale (10 × 75 m ). Each local P. substriatus population has a relatively short expected persistence time, but persistence of the species occurs due to a balance between frequent local extinctions and recolonizations. This nonequilibrium population structure can have profound effects on how the genetic variation is structured between and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 36 publications
3
52
1
Order By: Relevance
“…An earlier study focused on the population structure of P substriatus over a small spatial scale (<1000 m2), corresponding roughly to a single population of the host plant Carex nigra (Ingvarsson et al, 1997). In that study we found evidence for a strong degree of differentiation among local I?…”
Section: Introductionsupporting
confidence: 49%
See 4 more Smart Citations
“…An earlier study focused on the population structure of P substriatus over a small spatial scale (<1000 m2), corresponding roughly to a single population of the host plant Carex nigra (Ingvarsson et al, 1997). In that study we found evidence for a strong degree of differentiation among local I?…”
Section: Introductionsupporting
confidence: 49%
“…The increase in genetic differentiation could be further enhanced if recurrent extinctions and recolonizations of local populations are frequent and especially if founders of new populations come from a limited number of sources (founders have a high probability of common origin, sensu Whitlock & McCauley, 1990). In an earlier study (Ingvarsson et a!., 1997) we have shown that local population turnover is common in P substriatus and that founders of new populations indeed have a high probability of common origin because they come from only one or two source populations. We also showed that local extinctions and recolonizations result in an 40 per cent increase in the degree of differentiation among populations on island 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations